The Cambridge history of Japan (Cambridge University Press, 1989)
The Nineteenth Century provides the most comprehensive account available in any Western language of Japan's transformation from a feudal society to a modern nation state. This volume traces the roots and course of political, social, and institutional change that took place in Japan from late Tokugawa times to the early twentieth century. During this period Japan, under pressure from the intrusive West, abandoned its policy of national seclusion and remodeled its institutions to build the strength necessary to join the great powers and to fashion an empire in East Asia. It was an era remarkable for sweeping changes undertaken in the name of tradition, symbolized by the shift of authority from the shogun as military hegemon to the emperor who professed to cloak his sacrosanct prerogatives in constitutional procedures. The volume consists of an interrelated collection of authoritative and analytical chapters by specialists in the history of nineteenth-century Japan that discuss the fissures in late feudal society, the impact of and responses to the West, the overthrow of the shogunal government, and the revolutionary changes that were instituted as defensive measures to strengthen the country against what seemed a dangerous competition with the Western world. All of the chapters are based on current research and were writeen for students and scholars as well as for general readers who do not have a specialized knowledge of Japanese history.